High seroprevalence of anti-DENV IgM in blood donors in an early outbreak in the Federal District of Brazil, 2019. Issue 10 (20th October 2021) - Cilião-Alves, Daiani Cristina; Barcelos, Stefhani Martins de; Bezerra, Ariádine Loraine Oliveira; Almeida, Isabella Santana; Silveira, João Vitor Martins; Alencar, Jessica Pereira de; Pimentel, Bárbara Maciel Sidou; Araújo, Wildo Navegantes de; Haddad, Rodrigo
Abstract : Dengue is endemic in Brazil, and several Brazilian cities are affected by frequent seasonal outbreaks of the disease. During the outbreaks the possibility of transfusion-transmitted dengue (TTD) is increased, mainly by the presence of asymptomatic or oligosymptomatic infections in eligible blood donors. The retrospective assessment of anti-DENV IgM and NS1 seroprevalence during a given time interval may indicate the need for measures for the previous screening of DENV infection in blood donors. In this context, we performed retrospective screening for anti-DENV IgM and NS1 in blood donors from the Federal District of Brazil during the early outbreak that occurred in 2019, the largest outbreak in recent years. In total, 450 blood donations were screened for anti-DENV IgM and DENV NS1 using commercial enzyme-linked immunosorbent assay kits (Panbio Dengue IgM Capture ELISA and Platelia Dengue NS1 Ag, respectively). Among the tested plasma samples, 16 % (72/450) presented anti-DENV IgM; no samples presented DENV NS1. Despite the apparent absence of antigenaemia in tested blood donations, the high prevalence of anti-DENV IgM highlights the importance of DENV screening in blood donors, principally during outbreak periods.